Systematic Literature Review (SLR ), Peningkatan Pengetahuan Tentang Donor Darah. - aina, Tasha; ., Usiono (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The number of people donating blood in Indonesia is relatively low, with the number of regular donors at 250 thousand compared to the population in Indonesia which has 230-240 million people (Ministry of Health of the Republic of Indonesia, 2019), this shows that awareness of voluntary blood donation among the public is still low . The aim of this research is to conduct a literature review, namely to provide information about blood donation and provide understanding to the public about carrying out blood donation. The technique used is the Systematic Literature Review (SLR) strategy, which aims to identify, review and evaluate all relevant research so as to answer research questions at specified stages. The conclusion obtained from the results of this research is that this community service activity is able to increase knowledge about blood donation in the community